Analysis of stress tolerance, competitive-anxiety, heart rate variability and salivary cortisol during successive matches in male futsal players - Ribeiro, B. L. L.; Galvão-Coelho, N. L.; Almeida, R. N.; dos Santos Lima, G. Z.; de Sousa Fortes, L.; Mortatti, A. L (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background This study aimed to compare the stress tolerance, competitive anxiety, heart rate variability and salivary cortisol before and during successive futsal competitive matches (3 matches in 4 days) in young male futsal players.